2012
DOI: 10.2118/141304-pa
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on Two-Way Coupled Fluid Flow and Geomechanics in Hydrate Deposits

Abstract: Coupled flow and geomechanics play an important role in the analysis of gas hydrate reservoirs under production. The stiffness of the rock skeleton and the deformation of the reservoir, as well as porosity and permeability, are directly influenced by (and interrelated with) changes in pressure, temperature and fluid (water and gas) and solid (hydrate and ice) phase saturations. Fluid and solid phases may coexist, which, coupled with steep temperature and pressure gradients, result in strong nonlinearities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…Work by Tran et al (2002) is an example of an iteratively-coupled reservoir-geomechanics simulation. Thomas et al (2003), Kim et al (2012) also suggested coupled flow-geomechanics simulations.…”
Section: Coupled Fluid-geomechanics Simulation Approachesmentioning
confidence: 94%
“…Work by Tran et al (2002) is an example of an iteratively-coupled reservoir-geomechanics simulation. Thomas et al (2003), Kim et al (2012) also suggested coupled flow-geomechanics simulations.…”
Section: Coupled Fluid-geomechanics Simulation Approachesmentioning
confidence: 94%
“…Then, it solves geomechanics, based on the solutions obtained at the previous flow problem. This sequential method can easily be implemented by the Lagrange porosity function  and its correction  (e.g., Kim et al (2012)), written as a form of the staggered approach as,  ,…”
Section: Numerical Implementationmentioning
confidence: 99%
“…Poromechanical effect can affect perturbation of effective stress. Pressure of incompressible fluid such as water is sensitive to small change in pore volume, and, in turn, the changes in pressure alter the effective stress regime, which induces material failure (e.g, Kim et al 2012). Permeability is also a strong function of the failure status, because material failure increases permeability significantly by several orders.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it solves geomechanics, based on the solutions obtained at the previous flow problem. This sequential method can easily be implemented by the Lagrange porosity function  and its correction  (Settari and Mourits, 1998;Kim et al, 2012a), written as a form of the staggered approach as,…”
Section: Numerical Implementationmentioning
confidence: 99%
“…To this end, we consider variations in not only permeability but also pore volume, which lead to dynamic permeability and porosity of the reservoirs, respectively. In particular, compaction in undrained condition such as low permeability induces the increase of pore-pressure, which can change effective stress fields significantly and may result in geological failure (Kim et al, 2012a). Compaction-induced shear failure by fluid production was also studied by Dusseault et al (2001) and Bagheri and Settari (2008).…”
Section: Introductionmentioning
confidence: 99%